Plasma homocysteine level and its genotypes as a risk factor for coronary artery disease in patients undergoing coronary angiography - Naghshtabrizi, Behshad (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Hyperhomocysteinemia has recently been identified as a risk factor for coronary artery disease. Some genetic variants (such as C677T polymorphism) are postulated in this regard. We studied the relation between hyperhomocysteinemia and the above genetic variant and risk of coronary artery disease (CAD) and also the number of involved vessels. MATERIALS AND METHODS: From a total of 90 patients, 45 showed angiographically documented CAD and 45 had clinical manifestations of CAD but a negative angiography. Blood homocysteine level and C677T polymorphism were evaluated by Enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (PCR) respectively. RESULTS: Homocysteine level was significantly higher in the case group (P < 0.001) but no correlation was found between its level and extent of CAD. More homozygote cases of C677T allele were detected in the case group which was not related to the extent of CAD either. CONCLUSION: Presence of hyperhomocysteinemia increases the risk of CAD but does not predict the extent of it.